Lignocellulosic Biomass Conversion to Syngas through Co-Gasification Approach - Monir, Minhaj Uddin; Azrina, Abd Aziz; Khatun, Fatema; Vo, Dai-Viet N.; Nadzirah, Mohd Mokhtar (CRC Press, 2021)
This chapter includes an up-to-date description of the conversion of lignocellulosic biomass into syngas using co-gasification process. Due to the increasing demand for energy and environmental crisis, alternative strategies for the development of energy are urgently needed. Lignocellulosic biomass, which is mostly available all over the world could play a significant role and valorized the non-biomass resources for syngas or alternative fuel production. The efficiency of an environmentally friendly co-gasification technique has been discussed in this chapter. Energy or exergy efficiency through co-gasification is greater than that of single biomass gasification, and recent scientific literature has agreed on the acceptability of the co-gasification process. The potential co-gasification feedstocks of biomass that would enhance the gasification process will be the non-biomass of coal, peat, charcoal and petcoke. Therefore, the co-gasification technique has the potential to produce syngas from lignocellulosic biomass combined with broadly targeted non-biomass feedstocks.